Envejecimiento normal - Reyes, Carlos Alberto (Revista Estomatología, 1993)
Normal aging is near health than patology; aging process is natural and is not a disease. Biologic aging have structural and functional changes, in human being these are macroscopic and microscopic changes. Psychosocial aging have psychological and social changes with the age. There are theories for biological and psychosocial aging. Longevityis an objetive foraged people when !ife style is healthy and is near to biologic and psychosocial normal aging.